Forms and functions of the system intrinsic phonetic and phonological reduplication in the text of the Qur'an (Context: Journal of Interdisciplinary Studies, 2025)
Reduplication of linguistic units at different levels is a widespread phenomenon both in Arabic in general and in the text of the Qur'an. Therefore, some of its forms, such as lexical repetition, syntactic parallelism, and reduplication at the semantic level, are frequently discussed in the literature as cohesive and text building devices. The main goal of this paper is the analysis of the forms and functions of system intrinsic forms of reduplication in Arabic, i.e. reduplication of grammatical morphemes, derivational patterns, and a specific form of root morpheme reduplication producing a unique semantic effect. The analysis is based on the analytical-descriptive method and the typological-functional approach. Although the reduplication of grammatical morphemes and derivational patterns originates from the core rules of the Arabic language system, the analysis presented in the paper shows that its usage plays a significant role in the text of the Qur'an. In addition to producing of the complex sound patterns of rhyme and rhythm, it also serves as a text-building and cohesive device, and a means of emphasis, reinforcing the content of the message by drawing attention to its form.